1998
DOI: 10.1086/515669
|View full text |Cite
|
Sign up to set email alerts
|

Scrapie Infectivity and Proteinase K‐Resistant Prion Protein in Sheep Placenta, Brain, Spleen, and Lymph Node: Implications for Transmission and Antemortem Diagnosis

Abstract: Probable transmission of bovine spongiform encephalopathy to humans has focused intense interest on all of the transmissible spongiform encephalopathies (TSEs) and how they spread. In all TSEs, an abnormal disease-associated, proteinase K-resistant protein referred to as PrP-res or PrPsc accumulates in brain. In some species, PrP-res accumulates in other tissues as well. Sheep placenta, brain, spleen, and lymph node were analyzed in detail for PrP-res and infectivity. Both were detected in all brain and spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
129
0
7

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 20 publications
7
129
0
7
Order By: Relevance
“…This may be because they are more likely to propagate scrapie within their £ock once a ¢rst case has been acquired. This is certainly consistent with long-standing hypotheses about the role of infected reproductive tissues in the spread of scrapie (Pattison et al 1972;Pattison & Millson 1961;Race et al 1998;Ikegami et al 1991;Hourrigan & Klingsporn 1996). However an alternative explanation is simply that farms that breed a large proportion of their £ock are more likely to keep infected animals for long enough to see clinical disease.…”
Section: Discussionsupporting
confidence: 83%
“…This may be because they are more likely to propagate scrapie within their £ock once a ¢rst case has been acquired. This is certainly consistent with long-standing hypotheses about the role of infected reproductive tissues in the spread of scrapie (Pattison et al 1972;Pattison & Millson 1961;Race et al 1998;Ikegami et al 1991;Hourrigan & Klingsporn 1996). However an alternative explanation is simply that farms that breed a large proportion of their £ock are more likely to keep infected animals for long enough to see clinical disease.…”
Section: Discussionsupporting
confidence: 83%
“…This observation is consistent with the well-recognized infectivity of fetal membranes. 32 Similar to Andreoletti et al, 2 PrP sc was found to be restricted to fetal tissues. Because placentomes were not analyzed specifically for macrophages, the possibility of PrP sc deposits occurring in macrophages of the (maternal) caruncle or at the interface between fetal and maternal tissues remains.…”
Section: Discussionsupporting
confidence: 65%
“…However, it has largely been concluded that autolysis does not compromise the accuracy of assays that detect the proteinase-resistant, pathogenic isoform of the prion protein (PrP res ). 2,5,7,8,12,16 It was hypothesized that over a relatively long period of time, exposure to heat may have a more substantial effect on PrP res immunodection than previously considered. The objective of the present study was to characterize PrP CWD detectability with time in brain samples subjected to heat in vitro as determined by Western blot.…”
mentioning
confidence: 99%